Atmospheric aerosols around three different types of coal-based industries: Emission parameters, cytotoxicity assay, and principal component analysis. (December 2018) - Saikia, Jyotilima; Roy, Sonali; Bordoloi, Manobjyoti; Saikia, Prasenjit; Saikia, Binoy K.
Abstract: The present paper describes a comparison of the air quality and aerosols emission parameters around tea processing, coke oven and brick kiln industries that use high sulphur coals in their processes. The concentrations of gaseous species (SO2, NO2, and NH3 ) and aerosols (PM2.5, PM10 and TSPM) along with the physico-chemical properties (Moisture, Ash, Volatile Matter, C, H, N, TS) of the feed coals are compared for these industries. The concentrations of the gases e.g. SO2, NO2 and NH3 emitted are observed to be higher in the coke oven and tea processing industries in comparison to the brick kiln industry. The mean PM10 and PM2.5 concentrations are found to be higher in the tea processing industry A, followed by the coke oven, tea processing industry B and lastly the brick industry. The Cytotoxicity (MTT) assay of the aerosols was performed for their risk assessment. Source apportionment was carried out by using Principal Component Analysis and a high factor loading was observed in Factor 1 with 58% total variance and was associated with the secondary aerosol sources. Highlights: The emission characteristics from three different types of coal-based industries were compared. In the aerosol samples collected, hazardous elements, PAHs, and cytotoxicity were examined. Source apportionment study was conducted by using Principal Component Analysis.